2021
DOI: 10.1055/s-0041-1735835
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Free Flap Reconstruction in an Academic versus a Community Setting

Abstract: Background Head and neck free flap reconstructions are complex procedures requiring extensive resources, and have the potential to be highly morbid. As such, it is imperative that they should be performed in an appropriate setting, optimizing outcomes while limiting morbidity. The aim of this study is to identify any disparities in the treatment outcomes of patients undergoing head and neck free flap reconstruction by a single surgeon in an academic versus a community hospital setting. Methods A retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Current research highlights this complexity, showing varied outcomes influenced by health care environments and socioeconomic tiers. For instance, Lewcun et al 11 observed a higher incidence of postoperative complications in community hospitals than in academic hospitals. Similarly, this study found that patients with an MHI less than $55,000 were more likely to experience postoperative complications and unplanned reoperations.…”
Section: Discussionmentioning
confidence: 99%
“…Current research highlights this complexity, showing varied outcomes influenced by health care environments and socioeconomic tiers. For instance, Lewcun et al 11 observed a higher incidence of postoperative complications in community hospitals than in academic hospitals. Similarly, this study found that patients with an MHI less than $55,000 were more likely to experience postoperative complications and unplanned reoperations.…”
Section: Discussionmentioning
confidence: 99%
“…14 A couple of studies have shown that free flaps can be performed safely in community hospitals with acceptable morbidity and mortality rates when compared to academic/teaching institutes (high-volume centres). 15,16 Potential barriers to free flap reconstruction can be classified into preoperative, intraoperative and postoperative (Table 4). One 17 This concept is important in a resource-constrained setting where judicious use of manpower can be rewarding for not only the residents but also the department or institution at large.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the Northeastern part of the country re‐emphasised the need for a trained team with adequate infrastructure to be able to deliver the best results 14 . A couple of studies have shown that free flaps can be performed safely in community hospitals with acceptable morbidity and mortality rates when compared to academic/teaching institutes (high‐volume centres) 15,16 …”
Section: Discussionmentioning
confidence: 99%